The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/chem.201903252
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence Switching in Small Organic Molecules

Abstract: The circularly polarized luminescence (CPL) switching is of significant interest for applications in security technologies and sensing devices. Small organic molecules (SOMs) show severala dvantages over metal complexes, supramolecular assemblies, and polymers. Therefore, the recent progress on the CPL switching in SOMs is here reviewed. The resultsa re summarized based on the strategies used to tune factors that influence the emission properties, and thus, to realize CPL switching. The strategies that have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 79 publications
1
110
0
Order By: Relevance
“…Though there have been some recent partial reviews (Ma J. L. et al, 2019;Sang et al, 2019), CPL emitters whose emission is switchable under various stimuli have not been comprehensively reviewed. To fill this gap, a review of switchable CPL behavior is presented herein, including the use of irradiation with light, host-guest interaction, metal ions, pH, temperature, and solvents as stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Though there have been some recent partial reviews (Ma J. L. et al, 2019;Sang et al, 2019), CPL emitters whose emission is switchable under various stimuli have not been comprehensively reviewed. To fill this gap, a review of switchable CPL behavior is presented herein, including the use of irradiation with light, host-guest interaction, metal ions, pH, temperature, and solvents as stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, CP-OLEDs based on chiral fluorescent emitters could not only successfully achieve the CPEL [17][18][19], but also have the advantages of long device lifetime, good stability and low efficiency roll-off. Moreover, chiral fluorescent molecules with CPL activities are also cheap and easily available [20][21][22][23]. However, the devices based on fluorescent emitters generally suffer low efficiencies for only 25% exciton utilization of the fluorophores (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Benefitting from the good luminescent properties and the chirality in the excited state, the enantiomers exhibited perfect mirror-image CPL signals with the g lum values of −5.9 × 10 −3 for (P)-HAI and +6.2 × 10 −3 for (M)-HAI, respectively. The g lum values of the enantiomers with rigid helical skeleton are larger than those of the most chiral luminophores with other chiral elements [20,21]. Therefore, the helicene enantiomers might be excellent chiral emitter candidates for CP-OLEDs with intense CPEL activities.…”
mentioning
confidence: 99%
“…Circularly polarized emission (CPL) is rarely observed in systems different from chiral organic molecules [ 15 ] and lanthanide complexes. [ 16 ] To the best of our knowledge, studies searching for CPL in chiral‐at‐metal BODIPY containing molecules has not been reported.…”
Section: Introductionmentioning
confidence: 99%